Making Possible the impossible: performative ideas and solutions in some Iannis Xenakis' percussion works (Per Musi, 2023)
This paper presents reflections on two emblematic works by Iannis Xenakis: Rebonds (1987-1989) and Okho (1989). The perpetuation of the myth of the impossible as a poetic trait of this composer’s production is the main justification for the practices of simplification and self-indulgence of the percussive community around his pieces. Rebonds led us to a more direct reflection around technical solutions to challenges found in the musical text: the double appoggiatura (drag) and the rolls on the wooden instruments. In Okho, we demonstrate the dynamic process of searching for timbres on the djembé, observing the tension of what was called ‘transplanting’ compositional material from a piece written to be played with drumsticks (Rebonds) to one played with bare hands. Having Irlandini (2020), Solomos (1996), Soteriou (2011) and Stasi (2011) as bibliographical references, the main goal of this paper is to present possible performance solutions for excerpts of percussion music by Xenakis that might evoke the notion of ‘impossible’.